The impact of variation orders on the cost of mosque construction projects in Perak, Malaysia: A case study / Mohd Nazri Abdullah ... [et al.] - Abdullah, Mohd Nazri; Syed Mustapa, Syed Haris; Zainal Abidin, Zaiwanizar; Shuib, Mohammad Nasharudine; Mamat, Mohd Esham (2022)
This research investigates the impact on costing from variation order of ten (10) mosques in Perak, Malaysia derived from different stakeholders. Variation order were treated variedly according to the conditions of contract of the particular construction. This study focused on mosque project in Perak as per Public Work Department condition of contract which is Public Work Department Form of Contract PWD203a 2010 with quantity and Public Work Department Form of Contract PWD203 2010 with drawings and specifications. Both of the article of agreement partakes different approach on variation order calculation specifically on cost incurred. This paper aims to analyze variation order towards the costing of mosque construction in Perak, Malaysia and identify the cost distribution among the stakeholders of the mosque constructions in Perak, Malaysia. Employing analytical research that adopted qualitative method of case study and document review, a total of 10 mosques were analysed in Perak, Malaysia. From the study, it was revealed that the total variation order cost for the ten (10) mosque is RM417,479.79. Some variations are either beneficial or detrimental to the overall contract sum. The order of ranks of stakeholders contributing to variation order cost starting from the highest contributor to the lowest contributor are civil engineering, mechanical and electrical engineering, client, architect, contractor, quantity surveyor and lastly government authorities.